Análisis comparativo del módulo CRM ODOO y CRM ZOHO Inventory para la gestión eficiente de la distribución de paquetería de la sucursal de Servientrega en la ciudad de Babahoyo. - Moreira León, José Alexander (2024)
The main objective of the following project is a comparative analysis of the CRM Odoo module and CRM Zoho Inventory for the efficient management of parcel distribution at the Servientrega branch in the city of Babahoyo in order to identify and select the most appropriate IT solution for the monitoring and control of inventory, as well as improvements in communication with the client about the service they receive. In this research, a descriptive approach is used when collecting and analyzing information from reliable sources such as books, theses and other academic studies uploaded to the web, and information is also collected within the official page of each of these platforms. In the results of this research, very important information was determined which helps to identify which of the two tools is the one that best meets the specific needs of the company by comparing their characteristics.